Does earlier acquisition of motor competence promote pubertal physical activity in Japanese elementary school children: A 4-year follow-up study. Issue 18 (17th September 2022) - Hikihara, Yuki; Watanabe, Masashi; Aoyama, Tomoko; Wakabayashi, Hitoshi; Hanawa, Satoshi; Omi, Naomi; Tanaka, Shigeho
ABSTRACT: This 4-year follow-up study investigated which profile of motor competence (MC) in early childhood more strongly correlated with moderate-to-vigorous physical activity (MVPA) in early pubescence. A total of 247 first-grade children (152 boys) aged 6 to 7 years old participated in the baseline measurement. MVPA was measured using an accelerometer annually until the fifth grade. Body fat percentage was assessed using dual-energy X-ray absorptiometry at baseline. MC included fundamental movement skills (FMS) and motor performance, which were assessed in terms of locomotor and object control. FMS was assessed by the Test of Gross Motor Development-2, while motor performance (locomotor: run, hop, jump, and side-step, object control: throw, kick, and hand dribble) was assessed by Japanese Physical Fitness and Motor Abilities Test at baseline. Multiple regression analysis showed that locomotor and object control performance were significant predictors of MVPA in later grades in boys but not in girls. These associations between locomotor performance and MVPA mainly remained significant after controlling for body fat and MVPA at baseline. FMS in both genders was not a significant predictor of MVPA in early pubescence. This study suggests that appropriate strategies for increasing MVPA from prepubescence to early pubescence may differ between boys and girls.